Quality, innovation and performance: an exploratory study - Fernandes, A.A.C.M. (2012)
The relationship between total quality management and innovation appears contradictory and complex. Literature suggests that conflicting arguments exist and while for some researchers, total quality management practices do not directly improve innovation, for others, there is a positive relationship between management practices of quality and innovation. Similarly, it remains to explain the influence of total quality management and innovation in the organizational performance. In this research, our goal is to understand the synergistic relationships between the three variables: total quality management, organizational innovation and organizational performance. This study is based on two exploratory interviews in two ISO 9000 certified SMEs (Small and Medium sized Enterprises): a Logistics Company and a Fuel Company (household fuel and equipment installation and maintenance). Based on the analysis of these interviews we present a set of propositions about the relationship between those variables. These propositions will support the formulation of hypotheses for future scientific studies in this area. Results of this research can be of high utility in understanding how the variables interact and their impact in different types of organizations.